2010
DOI: 10.1016/j.neuron.2009.12.021
|View full text |Cite
|
Sign up to set email alerts
|

SynDIG1: An Activity-Regulated, AMPA- Receptor-Interacting Transmembrane Protein that Regulates Excitatory Synapse Development

Abstract: Summary During development of the central nervous system, precise synaptic connections between pre- and postsynaptic neurons are formed. While significant progress has been made in our understanding of AMPA receptor trafficking during synaptic plasticity, less is known about the molecules that recruit AMPA receptors to nascent synapses during synaptogenesis. Here we identify a type II transmembrane protein (SynDIG1) that regulates AMPA receptor content at developing synapses in dissociated rat hippocampal neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
143
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(154 citation statements)
references
References 39 publications
7
143
1
Order By: Relevance
“…Currently identified AMPAR auxiliary subunits include TARPs, suppressor of lurcher (SOL) 110 , Cornichon homologues (CNIHs) 111 , synapse differentiation-induced genes (SynDIG I and SynDIG4) 112,113 , cysteine-knot AMPAR modulating protein family 114,115 , and germ cell-specific gene 1-like (GSG1L) protein 116 . Of these the prototypical TARP family of AMPAR auxiliary subunits are by far the best characterized.…”
Section: Ampar Auxiliary Subunitsmentioning
confidence: 99%
“…Currently identified AMPAR auxiliary subunits include TARPs, suppressor of lurcher (SOL) 110 , Cornichon homologues (CNIHs) 111 , synapse differentiation-induced genes (SynDIG I and SynDIG4) 112,113 , cysteine-knot AMPAR modulating protein family 114,115 , and germ cell-specific gene 1-like (GSG1L) protein 116 . Of these the prototypical TARP family of AMPAR auxiliary subunits are by far the best characterized.…”
Section: Ampar Auxiliary Subunitsmentioning
confidence: 99%
“…These data further supported the notion that, in the heteromeric GluA1/A2 receptor, the dimer of dimers interface in LBDs is between GluA1 subunits. AMPARs are modulated by auxiliary subunits in the brain, including TARPs, cornichons, GSG1L, SynDIG1, CKAMP44, and other proteins (23)(24)(25)(26)(27)(28). Among them, TARPs are reported to affect AMPAR synthesis, maturation, trafficking, and function (29).…”
Section: Glua1 and Glua2 Have Preferred Positions In Tetrameric Assemmentioning
confidence: 99%
“…They can modulate the functional characteristics of iGluRs and may also mediate surface trafficking and/or targeting to specific subcellular compartments (Jackson and Nicoll 2011). Auxiliary proteins described so far include stargazin and its relatives (Tomita et al 2003;Milstein and Nicoll 2008), cornichon homolog-2 and homolog-3 (Schwenk et al 2009), Cysteine-knot AMPAR-modulating protein (von Engelhardt et al 2010), SynDIG1 (Kalashnikova et al 2010), neuropillin and tolloid-like proteins Neto1 and Neto2 (Ng et al 2009;Zhang et al 2009), and Caenorhabditis elegans SOL-1 (Zheng et al 2004). Studies in tissue culture and heterologous systems suggested that some of the auxiliary subunits have the potential to contribute to clustering of iGluRs, since they promote the accumulation of receptors at the cell surface (for review, see Jackson and Nicoll 2011).…”
mentioning
confidence: 99%